1336 TOWARDS AN UNDERSTANDING OF THE BIOLOGICAL MECHANISMS OF DELIRIUM USING FUNCTIONAL MRI: PILOT STUDY. (16th January 2023) - Ward, S; Van der Meer, J; Thistlethwaite, S; Greenwood, A; Appadurai, K; Kanagarajah, S; Watson, G; Adam, R; Campbell, M; Eeles, E; Breakspear, M
Abstract: Introduction: Delirium is a common condition in older hospitalised patients causing high morbidity and mortality. The neurobiological basis for delirium is uncertain and, for numerous reasons, research in this area has been limited. Several recent studies have demonstrated that functional neuroimaging in delirium is achievable and has suggested that a brain region termed the default mode network (DMN), may play a cardinal role in delirium pathogenesis. We set out to develop a pilot study to demonstrate that it is feasible to undertake functional magnetic resonance imaging (fMRI) scans in older patients with acute delirium. Methods: Observational pilot study obtaining a fMRI scan of inpatients in an Australian, tertiary hospital, geriatric ward. Eligible patients diagnosed as delirious by a geriatrician were compared against non-delirious controls. Informed consent was obtained. A novel scanning paradigm was developed. Sequences assed brain structure and functional networks in resting state and during a simple task of sustained attention and response inhibition. Results: 11 participants have been scanned. 6 participants were delirious: mean age 81 years (range 77 – 85 years), 3 female. 5 participants were non-delirious: mean age 83.4years (range 79 -90 years), 2 female. 10 of the 11 participants completed the full imaging protocol, including task engagement. Head movement during scanning, was generally within acceptable limits. Data demonstrates considerable cortical atrophy and ventricular enlargement consistent with age. Preliminary fMRI analyses show a variable pattern of cortical recruitment during task engagement in delirious patients. Conclusions: These findings show it is ethically and logistically feasible to engage elderly patients with acute delirium into a high end structural and functional imaging study.